Identifying the barriers to nursing power in hospitals - Campbell, Marie (Operating Room Nurses Association of Canada Journal, 1990)
This article is about power, specifically about the power of operating room nurses and how they exercise it in today’s high-tech environment. The prospects for nurses being more inﬂuential in determining how ORs should run will be addressed, as will how the worklife of nurses might be better organized.